On the possible cause of weight loss in treated insects. - Sharma, V. P.; Chattoraj, A. N. (Contributions to Entomology = Beiträge zur Entomologie, 1964)
Insects treated with insecticides loose water at a significantly higher rate than the normal and control run insects. A general shrinkage in all the tissues suggests that the loss in weight presumably, may be caused due to the loss of water from the general body tissues rather than by the epidermal cells alone. The theory has been advanced that the water loss may be caused due to the withdrawal of water from the tissues accompanied by the liberation of water, if any, due to the direct chemical action of insecticides. The water thus released inside the body of the insects, presumably increases the pressure from within of the insects, and this increased pressure allows the water to go out on the surface of the body, through the helical canals, where from, it evaporates.